Produção de biossurfactante por Bacillus subtilis UCP 0999 em sbstratos não convencionais e de baixo custo - Acioly, Leonila Maria Leandro (2009)
The biosurfactants biopolymers are used in various industrial sectors, but still, are not economically competitive with synthetic surfactants, due to high production costs, where the substrate is 30% of the final costs. In search of alternative and low cost in the present study, we investigated the sources agribusiness, rice bran (Oryza sativa), potato (Solanum tuberosum) and soybean (Sorghum vulgare), as a liquid medium for biosurfactant production by Bacillus subtilis UCP0999. Assays were performed with and without the addition of (2g / L), peptone, ammonium sulfate and either (0.01 mL / L) of micro-nutrients, which were inoculated with 5% of a culture of B. subtilis (106 CFU / mL), kept under orbital agitation of 200 rpm for 30 ° C for 72 h. At the end of fermentation, the cells collected corresponded to biomass and metabolic cell-free liquid were evaluated pH, surface tension, emulsification index (motor oil, diesel and kerosene) and extracting the biosurfactant produced. The results showed that the bacteria used and the rice bran supplemented with soy peptone, producing a surfactant to reduce surface tension of water to 72 mN / m to 37.80 mN / m and 37.70, respectively. The soy supplemented with micronutrients to reduce the tension 35.60 mN / m. On the other hand, when the used rice bran supplemented with nutrients and micro ammonium sulfate produced a greater quantity of biosurfactant with 8.60 and 6.1 g / L, respectively, showing no significant results regarding the reduction of surface tension . The biosurfactants produced showed high emulsification in motor oil, kerosene and diesel with values from 30 to 100%, with the highest rates with potato broth and soy supplemented with micronutrients and ammonium sulphate. The biosurfactant produced in the different media formulated demonstrated great potential for emulsification of hydrophobic substance and surface tension reduction, allowing for future use in bioremediation processes.